A Java GUI for the Design of an Impeller - Bramantya M. A.; Zahari Taha; Yasuo Suga (Jurnal Energi Dan Manufaktur, 2007)
Graphical User Interface (GUI) elements are treated as objects. They encapsulate data and method in a simple window. The GUI developed in this paper is to assisting designing and manufacturing an impeller pump. The software is developed in JAVA. Programming in JAVA takes advantages of its flexibilities. Results are presented in 2 D graphics and animation. Cubic Bezier curves algorithm is used to generate the impeller curve. The software is suitable for small industries and educational purposes.